Physical mapping of Malacosoma neustria nuclear polyhedrosis virus genome and its modification in Antheraea pernyi cell culture - Kikhno, I.M; Strokovskaya, L.I.; Meleshko, R.A.; Michalic, J.; Solomko, A.P. (Біополімери і клітина, 2002)
A physical map of the M. neustria nuclear polyhedrosis virus (ManeNPV) genome was constructed, the complete order of BamHl, Kpnl and PstI restriction enzyme sites was determined, a polyhedrin gene was localized on the map. The viral DNA size was calculated to be about 139 kbp. Restriction endonuclease profiles of the DNA of ManeNPV plaques isolate propagated in A. pernyi cells demonstrated "persistent heterogeneity", submolar bands were shown to appear in a digestion pattern of DNA of the first passage virus. These bands were proved to be due to the DNA molecules presence in the non-homogeneous virus DNA pool, their chains having been shown to carry a putative break in a definite site. Such a "break site" was localized on the physical, map of ManeNPV genome. Складено фізичну карту геному вірусу ядерного поліедрозу М. neustria (ManeNPV), визначено розташування сайтів для рестриктаз BamHl, Kpnl та PstI, на карті локалізовано ген поліедрину. Розмір вірусної ДНК визначено приблизно в 139 тис. п. н. Профілі рестриктів ДНК ManeNPV, ізольованих з бляшок, отриманих у клітинах A. pernyi, демонструють «тривку гетерогенність», субмолярні фрагменти виявлено в паттерні рестрикції після першого пасажу вірусу. Встановлено, що ці фрагменти присутні в пулі гетерогенної вірусної ДНК, а її нитки мають розриви в певному місці. Таке місце розриву було локалізовано на фізичній карті геному ManeNPV. Составлена физическая карта генома вируса ядерного полиэдроза М. neustria (ManeNPV), определено расположение сайтов для рестриктаз BamHl, Kpnl и PstI, на карте локализован ген полиэдрина. Размер вирусной ДНК определен приблизительно в 139 тыс п. к. Профили рестриктов ДНК ManeNPV, изолироанных из бляшек, полученных в клетках A. pernyi, демонстрируют «устойчивую гетерогенность», субмолярные фрагменты обнаружены в паттерне рестрикции после первого пассажа вируса. Установлено, что эти фрагменты присутствуют в пуле гетерогенной вирусной ДНК, а ее нити имеют разрыв в определенном месте. Такое место разрыва было локализовано на физической карте генома ManeNPV.